Implementation Of Hand Puppet Learning Media In Growing Islamic Character Of Elementary School Students Of Alam Friends Of The Quran - Aziz, Mursal; Hairullah; Cici Khumayroh Nasution (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to examine the implementation of hand puppet learning media in fostering students' Islamic character at SD IT Alam Sahabat Alquran. Using a descriptive qualitative approach with a case study method, this study involves participatory observation, in-depth interviews, and document analysis. The results of the study show that the use of hand puppets as a learning medium is effective in improving students' Islamic character, especially in the aspects of honesty, discipline, empathy, patience, and responsibility. This media has been shown to attract students' attention, facilitate understanding of abstract concepts, and encourage active participation in learning. The main challenges in implementation include time constraints and the need for content variation, which is overcome through teacher training and the development of a learning content bank. This study concludes that hand puppet learning media has significant potential in Islamic character education and recommends further development and integration with digital technology to increase its effectiveness.